Microscale Experiment and Pore-Network Modeling Analysis of Growth Habit, Pore Structure, and Permeability of Hydrate-Bearing Sediments - Kou, Xuan; Li, Xiao-Sen; Wang, Yi; Wan, Kun; Chen, Zhao-Yang (Energy & Fuels, 2021)
Pore structure properties of hydrate-bearing sediments considerably affect fluid flow properties during gas production from natural gas hydrate reservoirs. Hence, it is important to investigate the evolution of pore structure characteristics and fluid flow properties in hydrate-bearing sediments under various conditions. In this study, the effects of particle size and hydrate saturation on hydrate growth habits, pore structure properties, and permeability reduction have been analyzed via microscale experiments (using X-ray computed tomography) and pore-network models. Experimental results reveal the pore-habit evolution of gas hydrate from grain-enveloping to pore-filling, as well as the homogeneous distribution of gas hydrate in pores with the increase in hydrate saturation and the decrease in particle size. It is noteworthy that the pore structure characteristics of hydrate-bearing sediments depend on the pore interconnectivity. The pore interconnectivity is closely related to hydrate saturation. Specifically, the volume of non-interconnected pore (dead-end pore first increases and then decreases with the increase in hydrate saturation. However, the pore interconnectivity appears to be less influenced by the hydrate occurrence for small particle sizes. Based on pore-network modeling results, the exponential distribution of pore volume and the normal distribution of throat channel length have been found. Additionally, the correlated equation of absolute permeability and particle size in the presence of gas hydrate has been first proposed. The prediction accuracy of the absolute permeability equation has been validated by experimental results in this work and experimental measurements from previous studies. These results provide valuable information and data for efficient and economic gas production from hydrate-bearing sandy or silt sediments of submarine.